Analyzing students’ experience in programming with computational thinking through competitive, physical, and tactile games: The quadrilateral method approach - Habib, M. A. a; Raja-Yusof, R. -J.; Salim, S. S.a; Sani, A. A. a; Sofian, H.; Abu Bakar, A. (Turkiye Klinikleri Journal of Medical Sciences, 2021)
The lack of computational thinking (CT) skills can be one of the reasons why students find themselves having difficulties in writing a good program. Therefore, understanding how CT skills can be developed is essential. This research explores how CT skills can be developed for programming through competitive, physical, and tactile games. The CT elements in this research focus on four major programming concepts, which are decomposition, pattern recognition, abstraction, and algorithmic thinking. We have conducted game activities through several algorithms that include sorting, swapping, and graph algorithms and analyzed how the game affects the student experience (SX) in understanding the CT concept in those algorithms. We have applied the quadrilateral method approach to the data collection and analysis. The data was obtained through observation, interview/survey based on six SX criteria (attention, engagement, awareness, satisfaction, confidence, and performance), and performances of the conducted game activities were compared. The results of the quadrilation of the data collected show a positive impact on the SX, highlight the effectiveness of the competitive, physical, and tactile game approach proposed in this research towards programming and CT skills development.